Loss‐of‐Function Mutations in NR4A2 Cause Dopa‐Responsive Dystonia Parkinsonism. Issue 5 (10th January 2020) - Wirth, Thomas; Mariani, Louise Laure; Bergant, Gaber; Baulac, Michel; Habert, Marie‐Odile; Drouot, Nathalie; Ollivier, Emmanuelle; Hodžić, Alenka; Rudolf, Gorazd; Nitschke, Patrick; Rudolf, Gabrielle; Chelly, Jamel; et al.
Abstract: Background: The group of dystonia genes is expanding, and mutations of these genes have been associated with various combined dystonia syndromes. Among the latter, the cause of some dystonia parkinsonism cases remains unknown. Objective: To report patients with early‐onset dystonia parkinsonism as a result of loss‐of‐function mutations in nuclear receptor subfamily 4 group A member 2 . Methods: Phenotypic characterization and exome sequencing were carried out in 2 families. Results: The 2 patients reported here both had a history of mild intellectual disability in childhood and subsequently developed dystonia parkinsonism in early adulthood. Brain magnetic resonance imaging was normal, and DATscan suggested bilateral dopaminergic denervation. Two frameshift mutations in NR4A2 were identified: a de novo insertion (NM_006186.3; c.326dupA) in the first case and another small insertion (NM_006186.3; c.881dupA) in the second. Conclusions: NR4A2 haploinsufficiency mutations have been recently reported in neurodevelopmental phenotypes. Our findings indicate that dystonia and/or parkinsonism may appear years after initial symptoms. Mutations in NR4A2 should be considered in patients with unexplained dystonia parkinsonism. © 2020 International Parkinson and Movement Disorder Society